Implications of Working Environment Job Stress Moderated Employee Engagement to Improve Employee Performance in the Electronic Transaction Service Industry - Yudi Nur Supriadi; Nashrin Urbach; Jumadil Saputra (International Business and Accounting Research Journal, 2022)
The purpose of the analysis is to prove the implications of the work environment and job stress that moderate employee engagement on improve employee performance. The sample of this research is 255 respondents of electronic transaction service industry employees in DKI Jakarta and Banten Provinces. The analysis technique used is the path analysis method and data processing is carried out through SmartPLS 3.0. The results of the study showed that the work environment and job stress had a positive effect on employee performance, but the work environment had a negative and insignificant effect on employee performance, moderated by employee engagement. While job stress has a positive and significant effect on employee performance, moderated by employee engagement, and has a positive effect on employees' performance. Novelty's findings resulted in a performance improvement model moderated by employee engagement. This research contributes that if the company wants to improve performance, it needs to be improved: a). Appreciate every employee who completes the task well. b). The quality of good relations between employees and management. c). A quiet work environment, a workspace that is free from noise so you can focus on doing your job, d). Increased awareness and willingness of employees to do work without being asked. Companies need to design the media as a means of existence for company management. Companies also need to design stress management programs by making employees happy. Companies must care about the health of employees.